Advances in smartphone-based point-of-care diagnostics - Xu, X.Y.; Akay, A.; Wei, H.L.; Wang, S.Q.; Pingguan-Murphy, Belinda; Erlandsson, B.E.; Li, X.J.; Lee, W.; Hu, J.; Wang, L.; Xu, F. (Institute of Electrical and Electronics Engineers (IEEE), 2015)
Point-of-care (POC) diagnostics is playing an increasingly important role in public health, environmental monitoring, and food safety analysis. Smartphones, alone or in conjunction with add-on devices, have shown great capability of data collection, analysis, display, and transmission, making them popular in POC diagnostics. In this article, the state-of-the-art advances in smartphone-based POC diagnostic technologies and their applications in the past few years are outlined, ranging from in vivo tests that use smartphone's built-in/external sensors to detect biological signals to in vitro tests that involves complicated biochemical reactions. Novel techniques are illustrated by a number of attractive examples, followed by a brief discussion of the smartphone's role in telemedicine. The challenges and perspectives of smartphone-based POC diagnostics are also provided.